A STUDY OF READING COMPREHENSION ACHIEVEMENT OF PUPILS IN KATSINA STATE - Hassan, S. O. (Sokoto Educational Review, 2020)
This study examined the degree of achievement of Primary school pupils in reading comprehension in Katsina State. The objectives were to know if primary fiv e pupils would read a set passage for primary three and what percentage of success would be recorded. A total of a hundred (100) pupils from five primary schools in fou r districts (LGAS) Daura, Katsina, Funtua and Charanclii were involved in the study. A passage titled Mohammed and the Cows from Macmillan English coursebook three was used with seven questions set on it. The t-test statistics instrument was employed to compute the comprehension exercise scores. The result showed that the pupils read at the mean average score of 0.4, - 3.3 as against the general mean of seven (7). The findings revealed that illiteracy problem is high in the State primary Schools. The pupils were unable to respond adequately to verbal instructions in the English language and were grossly unable to do the reading comprehension exercise. This study is significant as it creates awareness about the critical level of illiteracy in schools. The primary school administrators would be better informed on the awful trend of pupils ’ failu re to read. The Government should promote literacy in the primary Schools through a state-wide literacy programme and the teachers should imbibe better teaching strategies even as they learn to use the English Language to communicate with pupils in upper primary schools throughout the state.